Paradox: Does liver insuffi ciency protect the patient? A hypothesis - A. M. Dzyadz'ko; A. E. Shcherba; O. O. Rummo; M. L. Katin; A. F. Minov; S. V. Korotkov; O. A. Chugunova; E. O. Santotskiy; D. Yu. Efimov; M. Yu. Gurova (Трансплантология (Москва))
Despite the fact that the key role of the liver in the formation of the immune response to injury is not in doubt, the mechanisms of weakening the immune response to infectious and noninfectious lesions in patients with hepatic failure remain unclear. We propose an original hypothesis of forming the ways to limit the amplitude of the systemic inflammatory response in patients with the end-stage liver disease. The basis of the hypothesis is the idea that as a result of reducing the intensity of the natural stimulation of membrane mCD14 receptors by the ligands of infectious nature, the basic mechanism of the systemic immune response induction by liver macrophages (Kupffer cells) is interrupted. According to the proposed hypothesis, in condition of liver failure, the synthesis of lipopolysaccharide-binding protein by hepatocytes is reduced. This leads to a decreased amplitude and intensity of the protective immune responses. This fact explains a number of clinical phenomena observed in patients with liver failure/dysfunction that consist in a reduced reactivity of the organism to the damage inflicted by infectious and noninfectious agents. The authors consider it possible to use this hypothesis in the search for new trends to prevent the immune system hyper-reactivity in sepsis, and to improve the therapeutic strategies for the management of patients at high risk of infectious complications after liver transplantation.